Protective effect of a silane-cement-based permeable crystalline composite coating on concrete structures under freeze-thaw chloride environments - Bo, Yang; Weihua, Li; Wenlong, Yan; Junkai, Wang; Lulu, Zhang; Lin, Geng; Tongfang, Wang; Zhenxiang, Qin; Tao, Fu (Frontiers in Materials, 2025)
In this study, the effects of surface treatment on concrete members with a silane-cement-based penetrant crystal composite coating were investigated. The protective effect of this composite coating was assessed via indoor durability tests and its influence on the service life of concrete structures was predicted. The results indicate that the silane-cement-based penetrant crystal composite coating can significantly reduce freeze-thaw damage to concrete, effectively delaying its onset while enhancing the resistance to chloride infiltration. While freeze-thaw cycles progressively weaken concrete’s survival capacity, the composite coating notably improves chloride ion erosion resistance—especially during early cyclic stages—by inducing microstructural densification and forming a surface protective layer. This may be attributed to the changes in the concrete microstructure during the initial stages and the protective layer formed by the coating on the surface. The coating permeability allows it to penetrate deep into the concrete, creating an effective barrier that minimises external chloride salt intrusion. This synergistic effect surpasses single-component coatings by integrating silane’s hydrophobicity with penetrant crystals’ self-healing properties, demonstrating superior resistance to coupled freeze-thaw and chloride attacks. In summary, the silane-cement-based penetrant crystal composite coating extends the service life of concrete structures and provides robust protection under harsh conditions, laying the groundwork for their practical use in engineering applications.